2018
DOI: 10.1007/s11517-018-1837-9
|View full text |Cite
|
Sign up to set email alerts
|

Hair detection and lesion segmentation in dermoscopic images using domain knowledge

Abstract: Automated segmentation and dermoscopic hair detection are one of the significant challenges in computer-aided diagnosis (CAD) of melanocytic lesions. Additionally, due to the presence of artifacts and variation in skin texture and smooth lesion boundaries, the accuracy of such methods gets hampered. The objective of this research is to develop an automated hair detection and lesion segmentation algorithm using lesion-specific properties to improve the accuracy. The aforementioned objective is achieved in two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Whereas, for image size 512 x 512, the average accuracy is 93.79% with average error rate 6.21%. The segmentation results of PH2 are also compared with existing methods such as (Pennisi et al, ) and (Pathan, Prabhu, & Siddalingaswamy, ) which shows that proposed method perform superior.…”
Section: Experimental Results and Analysismentioning
confidence: 92%
“…Whereas, for image size 512 x 512, the average accuracy is 93.79% with average error rate 6.21%. The segmentation results of PH2 are also compared with existing methods such as (Pennisi et al, ) and (Pathan, Prabhu, & Siddalingaswamy, ) which shows that proposed method perform superior.…”
Section: Experimental Results and Analysismentioning
confidence: 92%
“…This is in disparity with the findings of studies, which stated that preprocessing is needed for efficient and robust analysis of skin lesions in dermoscopic images [ 17 , 21 , 34 ]. A plethora of studies have showed the huge impact of preprocessing to significantly increase the skin lesion segmentation results [ 9 , 21 , 23 , 34 , 40 , 47 , 69 , 87 , 89 , 90 ]. Conversely, the results of this study support the findings of [ 91 ] that the preprocessing effect is dependent on segmentation and postprocessing methods employed.…”
Section: Discussionmentioning
confidence: 99%
“…However, among all, detection of lesions from dermoscopy images is a challenging task from the last few years, and various techniques are developed by several researchers using computer vision (CV) and machine learning (Amin, Sharif, Yasmin, Saba, & Raza, ; Amin et al, ; Husham, Alkawaz, Saba, Rehman, & Alghamdi, ; Iqbal et al, ; Iqbal, Ghani, Saba, & Rehman, ; Iqbal, Khan, Saba, & Rehman, ; Jamal et al, ; Fahad et al, ). Pathan, Prabhu, and Siddalingaswamy () developed a novel hair detection and segmentation method by utilizing specific properties of the lesion. Their work is composed of two parts.…”
Section: Related Workmentioning
confidence: 99%